2016
DOI: 10.4238/gmr.15038293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dual Bt-expression transformation vectors on transgene expression in tobacco

Abstract: ABSTRACT. This study aimed to determine the influence of vector structure on dual Bt gene expression and establish an efficient expression vector using Cry1Ac and Cry3A genes. Four vectors (N4, N5, N10, and S23) were developed and used for genetic transformation of tobacco to obtain insect-resistant transgenic lines. The vectors were constructed using the MAR structure, applying different promoter and enhancer sequences, and changing the transgene open-reading frame sequence. The average Cry1Ac toxalbumin expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, crops with gene stacking have been planted in many countries; however, the combination of multiple genes may also lead to mutual interference between genes, causing one gene to inhibit the other gene. According to previous research, a comparison and analysis of the expression of exogenous genes in four double Bt gene vectors, showed that the expression level of the Bt gene was low when it was located upstream of T-DNA [ 36 ]. With the development of transgenic technology, it is necessary to note whether gene stacking transgenic plants are safer than single gene transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, crops with gene stacking have been planted in many countries; however, the combination of multiple genes may also lead to mutual interference between genes, causing one gene to inhibit the other gene. According to previous research, a comparison and analysis of the expression of exogenous genes in four double Bt gene vectors, showed that the expression level of the Bt gene was low when it was located upstream of T-DNA [ 36 ]. With the development of transgenic technology, it is necessary to note whether gene stacking transgenic plants are safer than single gene transgenic plants.…”
Section: Discussionmentioning
confidence: 99%